• f(x) is simply some mathematical operation you are applying to the variable x so f(x)= 4*x^2 implies that we are taking x (whatever x may be) and multiplying it with itself (x * x = x^2), then multiplying that quantity by 4. x-1 is simply a different variable to which we are applying the same mathematical operation so f(x-1) = 4 *(x-1)^2 = 4 * ((x-1)*(x-1)) I'll leave it to you to do the actual multiplication. I hope this helps.
  • OK this is how to do it: we are told F(x) = 4x^2 (x^2 same as saying x squared) So that is the function definition. Whatever x is, square it and then multiply by 4. That will give you F(x) for any x. x could be 4 say which gives F(4) = 4 * 4^2 = 4 * 16 = 64 when you place 4 instead of x or x =3 F(3) = 4* 3^2 = 4*9 = 36 when you place 3 instead of x What about x = y say? Same again... F(y) = 4* y^2 or x = x-1 (don't panic! do exactly the same as before!) F(x-1) = 4 * (x-1)^2 You can then expand this out if you wish = 4 * (x-1)*(x-1) = 4 * (x^2 -2x +1) = 4*x^2 - 8x +4 Make sense? EDIT sorry I made a schoolboy error there lol
  • f(x)=4x^2 f(x-1)=4(x-1)^2 =4(x^2-2x+1) =4x^2-8x+4 i think dis is correct
  • f(x)=4x^2 now f(x-1)=4(x-1)^2 =4(x^2-2x+1) =4x^2-8x+4 thats is so simple
  • 4(x-1)squared answer: 4x squared -4 because 4*x = 4x squared then 4*-1 = -4
  • F(x-1) to evaluate f=4(x)2 simply you have to put the value of x in it. (x-1)=0 x = 1 so put it in f=4(x)2 f=4(1)2 square root of 1 is 1 answer is 4. if the square take full square of 4x then its 16.
  • f(x-1)=4x^2 =4(x-1)^2 =4(x^2-1) f(x-1)=4x^2-4 -----that's the correct answer, i think only one got the correct answer except me, -this is the question that made your head break? ooooohhhhhh!!!!come on!

Copyright 2020, Wired Ivy, LLC

Answerbag | Terms of Service | Privacy Policy